Die Bevordering van gemeenskapsverhoudinge deur die suid-afrikaanse polisiediens (ovs-streek) : - Rhyne Rhyne Kriek (Communicare)
The Image of an organization - the aggregate of the perceptions of target publics regarding an organization currently plays a decisive role in the functioning and successful, continued existence of the organization Although the image of an organization is determined by a myriad of variables, the primary aim of this study was to investigate the way in which the South African Police Service (OFS Region) applied specific specialized fields of public relations in the management of image In order to enhance community relations, with specific reference to the role of public relations as a business activity in this regard. The management of the following five specialized areas of public relations is relevant: strategic corporative communication, public opinion and issues, social involvement, change, and crisis communication. Some of the findings, conclusions and recommendations, based on a literature study and semi-structured